Phenomenology Study: Learning English Vocabulary Strategies Through Action-Adventure Video Games - Wianto, Denny; Alpianur, Alpianur; Rafidiyah, Dina (Eduinfo Media, 2022)
This research is a phenomenology study about how two teens who like to play the action-adventure video game “La Noire” gained new vocabularies in English. The game is about criminal cases that happened in Los Angeles after World War II. An in-depth interview was used to dig into the teens’ experiences to describe how they learned new vocabulary while playing the game. The results are that both participants liked the game and were curious about the cases, so they got attached and played for long times, around 3-6 hours. Sometimes they use a dictionary to find the meaning, but mostly they try to solve it from the context of the situation while they play the game. The repetition of the new vocabularies makes them maintain those vocabularies even though they also can pick up slang language and new culture. The next research may describe more about which kind of culture that interesting to learn new vocabulary.